2019
DOI: 10.19166/nc.v6i2.1907
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Attitude and Motivation With the Implementation of Sbar Communication Technique Done by Emergency Room Nurses While Doing Patient Handover in a Private Hospital in West Region of Indonesia

Abstract: <p>The effective communication increase is one of the seven goals of patient safety. The SBARcommunication technique is part of it. There are several factors that influence the application of SBAR communication namely; knowledge, attitude and motivation. According to the Joint Commission International (JCI) and the World Health Organization (WHO) of 25,000-30,000 cases of permanent disability in patients in Australia, 11% was due to communication failure. Based on interviews by researcher with head nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The nurses who have a good attitude have 2.647 times the opportunity to improve the application of the SBAR method. This study is similar to the study conducted in Indonesia that attitude will affect a person's ability to convey information that has an impact on good communication (Rut et al, 2019). Thus, the attitude has an important role for nurses when communicating with both the patient or the medical staff.…”
Section: Discussionsupporting
confidence: 77%
“…The nurses who have a good attitude have 2.647 times the opportunity to improve the application of the SBAR method. This study is similar to the study conducted in Indonesia that attitude will affect a person's ability to convey information that has an impact on good communication (Rut et al, 2019). Thus, the attitude has an important role for nurses when communicating with both the patient or the medical staff.…”
Section: Discussionsupporting
confidence: 77%
“…It has been seen in previous studies that emergency room nurses prevented communication problems, medical mistakes and data loss by careful handover [6,7,17]. In addition, it was found that careful and accurate handover increased the quality of the information conveyed and the reliability of the treatment [8].…”
Section: Introductionmentioning
confidence: 91%
“…However, during the handover process of patients among nurses in emergency rooms, there may be some deficiencies for various reasons. Patients in critical condition who have minimal physiological well-being require on-time acute care [7,8], and handover in an emergency situation may be the only chance for nurses to transfer patient information in a limited time [9]. Due to all these factors, handover in emergency situations causes alarming concern in terms of patient safety not only for researchers, but also for emergency room health care workers and national and international organizations [10].…”
mentioning
confidence: 99%